Design and Optimization Based on Monte Carlo Method of a Range Shifter for Proton Therapy. (1st February 2021) - Yu, Yecheng; Tan, Ping; Lin, Yinjie; Hu, Yuying; Guo, Huidong; Lei, Hao; Zhang, Zhongqi; Li, Jiadong; Hu, Delin
Abstract: A proton therapy facility based on an isochronous superconducting cyclotron is under constructed at the Proton Therapy Facility of the Huazhong University of Science and Technology. Due to the limitation of minimum energy extracted by the energy selection system in the upstream beamline, a range shifter is installed at the end of the nozzle to further decrease the proton beam energy so that the shallow-seated tumors can be treated. In this paper, the physical structure, energy degradation scheme, and material optimization selection of the range shifter are discussed and analyzed by Monte Carlo simulation software Geant4 and FLUKA. At the same time, the treatment outcome on the energy degradation process and its influence on the synthesis of spread-out Bragg peak (SOBP) in the treatment plan system after the application of the range shifter are analyzed. The results show that by using a high-density polyethylene energy-degrading plate with a thickness of 42.35 mm, combined with two 30-mm copper collimators, the range shifter can achieve a good energy-degradation effect while significantly reducing the beam horizontal penumbra at the edge of the radiation field. At the same time, the addition of the range shifter can reduce the number of the energy level required to form the SOBP and shorten the treatment time, but it will inevitably lead to a slight increase in the longitudinal penumbra.